2017
DOI: 10.3389/fcell.2017.00059
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled Paralogs in Vertebrate Development: Redundant or Distinct?

Abstract: Dishevelled (DVL) proteins are highly conserved in the animal kingdom and are important key players in β-Catenin-dependent and -independent Wnt signaling pathways. Vertebrate genomes typically comprise three DVL genes, DVL1, DVL2, and DVL3. Expression patterns and developmental functions of the three vertebrate DVL proteins however, are only partially redundant in any given species. Moreover, expression and function of DVL isoforms have diverged between different vertebrate species. All DVL proteins share basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 81 publications
(126 reference statements)
0
21
0
Order By: Relevance
“…Interestingly, even though DVL-1 is one of the least abundant of the total DVL protein pool, it has been shown to play an imperative role in stimulating LRP6 phosphorylation and activation of the Wnt transcriptional activity 11,12 . DVL is not only critical in human development 13 and key physiological processes, but its altered expression has been demonstrated in some tumours relative to non-transformed cells and linked with various cancer types 3,14,15 . Even though DVL proteins bridge critical Wnt signals with nuclear responses, how it is regulated is poorly understood 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, even though DVL-1 is one of the least abundant of the total DVL protein pool, it has been shown to play an imperative role in stimulating LRP6 phosphorylation and activation of the Wnt transcriptional activity 11,12 . DVL is not only critical in human development 13 and key physiological processes, but its altered expression has been demonstrated in some tumours relative to non-transformed cells and linked with various cancer types 3,14,15 . Even though DVL proteins bridge critical Wnt signals with nuclear responses, how it is regulated is poorly understood 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signals are transduced via the membrane receptor Frizzled (FZD) and the intracellular protein Dishevelled (Dsh in Drosophila , DVL1–3 in humans). There is a general agreement based on strong genetic evidence in Drosophila 3 and mouse 5,6 that DVL protein(s) plays a crucial role in all major branches of Wnt signaling and serves as a signaling hub.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Dishevelled proteins, such as Dvl1, Dvl2, and Dvl3, act as adaptors (or scaffold proteins) that are working in partnership with Fzd (an integral membrane protein) to create the PCP protein complex of Fzd/Dvl, which in turn induces Wnt signaling downstream, having a crucial role to support development, tissue regeneration, cellular homeostasis, and an array of other cellular processes 4648 . However, the precise biological function of Dvl proteins remains a mystery after more than two decades of studies 49 .…”
Section: Discussionmentioning
confidence: 99%